Analysis of the Potent Prognostic Factors in Luminal-Type Breast Cancer - Kim, Han-Sung; Park, Inseok; Cho, Hyun Jin; Gwak, Geumhee; Yang, Keunho; Bae, Byung Noe; Kim, Ki Whan; Han, Sehwan; Kim, Hong-Joo; Kim, Young-Duck (Journal of breast cancer, 2012)
Luminal-type breast cancer has a good prognosis compared to other types, such as human epidermal growth factor receptor 2 and triple negative types. Luminal-type breast cancer is classified into luminal A and B, according to the proliferation index. We investigated the clinicopathological factors that affect the prognosis of the luminal-type subgroups. We reviewed the medical records and the pathologic reports of 159 luminal-type breast cancer patients who were treated between February 2005 and November 2007. We divided luminal-type breast cancer into luminal A and B, according to Ki-67 (cutoff value, 14%) and analyzed the clinicopathologic factors, such as age at diagnosis, intensity score of estrogen receptor and progesterone receptor, histologic grade, and Bcl-2. Moreover, we compared the disease-free survival (DFS) of each group. In the univariate analysis, age (p=0.004), tumor size (p=0.010), lymph node metastasis (p=0.001), and Bcl-2 (p=0.002) were statistically significant factors in luminal-type breast cancer. In the multivariate analysis, lymph node (p=0.049) and Bcl-2 (p=0.034) were significant relevant factors in luminal-type breast cancer. In the subgroup analysis, the increased Bcl-2 (cutoff value, 33%) was related with a longer DFS in the luminal B group (p=0.004). In our study, luminal A breast cancer showed a longer DFS than luminal B breast cancer, further, Bcl-2 may be a potent prognostic factor in luminal-type breast cancer.